2020
DOI: 10.1088/1361-6641/ab9db5
|View full text |Cite
|
Sign up to set email alerts
|

Operational transconductance amplifier designed with nanowire tunnel-FET with Si, SiGe and Ge sources using experimental data

Abstract: In this paper operational transconductance amplifiers (OTA) were designed with nanowire (NW) tunnel field effect transistors (TFET) with different source materials (Si, SiGe, and Ge) and compared with NW Si MOSFET devices. Lookup tables with experimental data were used to model the transistors and simulate the OTAs. At the same dimensions and transistor efficiency region, the TFET OTAs have larger gain than the MOSFET circuit. The Ge-source TFET OTA presents the highest differential gain (105 dB), followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the NW-MOSFET a range from 0 V to 1.5 V were used in both V GS and V DS . More information on the current and capacitance measurements are described in [13,28,29].…”
Section: Devices Model and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the NW-MOSFET a range from 0 V to 1.5 V were used in both V GS and V DS . More information on the current and capacitance measurements are described in [13,28,29].…”
Section: Devices Model and Characteristicsmentioning
confidence: 99%
“…It has been shown that analog circuits designed with TFETs have high voltage gain and consume much less power [10][11][12][13][14]. Despite the promising results, silicon TFETs have low on-state current, which degrades TFET circuits frequency response and drive capability, therefore a technology with both TFET and MOSFET devices on silicon can take advantage of the best features in each device [15].…”
Section: Introductionmentioning
confidence: 99%
“…All devices have a gate oxide composed by 1.8 nm of HfO2 on top of 1 nm of SiO2. The transistor characteristics from a device perspective can be found in [5], [17]- [20]. The devices model and validation are described in [5].…”
Section: Devices Characteristicsmentioning
confidence: 99%
“…based on experimental curves of drain current as a function of the gate and drain voltage with a very small step. Although this is a relatively new approach to simulated devices that did not have a good model to predict their behavior, some works that also used the LUT method for simulating the behavior of other devices inside analog circuits as well, such as the circuits designed with Tunnel-FET [13][14][15].…”
Section: Introductionmentioning
confidence: 99%